PERAN KOMUNIKASI KELOMPOK BERBASIS GENDER (Studi Akses Informasi Kelompok Perempuan Nelayan di Wonorejo, Banyuputih Situbondo, Jawa Timur) - Nur Ainiyah (MUWAZAH : jurnal kajian gender, 2016)
This study aims to explore the role of gender-based group communication. The theory used was group communication, gender communication and information theory. This research was using qualitative approach. Data collection techniques using observation, interviews and documents. The results showed that, the reality of women fishermen actively involved in gathering groups, cooperatives and groups develop themselves. The process of women's access to information, receive and process information must be notified in advance because, knowing the importance or whether only personal information. The role of group communication of the fishing communities women are at least three that conformity, social facilitation and polarization.